Acute kidney injury and in-hospital outcomes after transcatheter aortic valve replacement in patients without chronic kidney disease: insights from the national inpatient sample - Congyan Ye; Xueping Ma; Bo Shi; Rui Yan; Shizhe Fu; Kairu Wang; Ru Yan; Shaobin Jia; Shengping Yang; Guangzhi Cong (BMC Cardiovascular Disorders)
Abstract Background Acute kidney injury (AKI) complicates transcatheter aortic valve replacement (TAVR), leading to higher mortality. The incidence and effects of AKI on clinical outcomes in patients undergoing TAVR without chronic kidney disease (CKD) are unclear. We aimed to determine the association between AKI and in-hospital outcomes in patients with TAVR using propensity score matching (PSM). Methods Using International Classification of Diseases-10th Revision codes, we queried the National Inpatient Sample for TAVR performed between 2016 and 2021. Patients were divided into two groups according to perioperative AKI development. Patients with CKD or on permanent hemodialysis at baseline were excluded. We conducted 1:1 PSM to assemble a cohort of patients with similar baseline characteristics. Multivariate logistic regression was used to assess the association between AKI and in-hospital outcomes. Sensitivity analysis was conducted to evaluate the robustness of our inferences. Results Of 47,372 unweighted patient admissions for TAVR, 1617 (3.41%) had a concomitant diagnosis of AKI. The incidence of AKI decreased from 4.82 to 3.18% from 2016 to 2021 (P-trend < 0.01). Before PSM, patients with AKI had a significantly higher rate of in-hospital mortality compared with those without AKI (6.12% vs. 0.48%, respectively; odds ratio [OR] 8.59, 95% confidence interval [CI] 6.32–11.68). Using the PSM algorithm, 1579 well-matched patients were included in each group. After PSM, an association was observed between patients with TAVR and concomitant AKI and a higher risk of in-hospital mortality (6.21% vs. 1.08%, respectively; OR 5.96; 95% CI 3.54–10.04). In subgroup analyses stratified according to age (≤ 80 and > 80 years), sex (male/female), and hypertension status, consistent associations were observed between AKI and the risk of in-hospital mortality. AKI patients were at higher risk for acute myocardial infarction (OR 1.78, 95% CI 1.35–2.34), major bleeding (OR 1.62, 95% CI 1.13–2.33), blood transfusion (OR 1.65, 95% CI 1.28–2.11), and cardiogenic shock (OR 3.73, 95% CI 2.77–5.01). No significant betweengroup differences were observed in stroke (P = 0.12). Conclusion AKI was a strong predictor of in-hospital mortality in patients undergoing TAVR without CKD and was associated with higher post-procedure complication rates.